WRITING GOOD TRAVEL ARTICLE TO PROMOTE TOURISM IN EAST JAVA GOVERNMENT CULTURE AND TOURISM SERVICE - Etika Nur Istiqomah, 151511813036 (2018)
From finding and discussion in the previous chapter, the writer presented a conclusion and some suggestions dealing with writing a good travel article which describes as follows: First, the writer learned the rules in making a travel article in East Java Government Culture and Tourism Service. The information in the article should brief, chronological and vivid. For the first time the writer wrote the article, she did not understand the context in a travel article. The solution was the writer read a tourism book titled Travel Manual: East Java Manual. This book published by East Java Government Culture and Tourism Service. The writer also noted some vocabularies which relate to tourism and searched the example of travel article on Cyber. Second, the writer also understood the aspects of making a good travel article. The article should follow these three aspects. They are subjective on point of view, contract of truthfulness, and double story. In this case, the writer succeeded writing the article by following the two of those aspects, subjective on point of view and contract of truthfulness. For more information, in this globalization era, those three aspects are being massive because the marketing business decided the strategy of writing travel article becomes beyond in supporting the information service to the societies. Last, the writer received several added values during the internship in East Java Government Culture and Tourism Service. The writer achieved the experience in making a travel article, having a chance to corporate with the staff in the marketing department, working in the institution as a team in the events of Tourist Information Center in Surabaya North Quay. In this events, the writer had the opportunity to apply her speaking skill to the international tourists from Asian and European. The writer also achieved the value in decision making because she realized that decision which taken in institution impacts bigger than in college